Virtual Tools Show Promise for Moving the Needle on Culturally and Linguistically Diverse Family Engagement - Tamra Mitchell; Socorro Herrera (The Advocate, 2020)
The school building closures of spring 2020 fundamentally disrupted education in Kansas, but out of this disruption emerged the need and opportunity for schools and educators to be creative and innovative. At a time when every parent in our state was either employed as an essential worker and working longer hours, trying to work from home, or trying to navigate the loss of their job, they were also trying to support their children with continuous learning. This required Kansas schools to think differently and try new strategies for truly engaging families. One promising innovation that many schools piloted was to host a virtual, interactive, and engaging un-conference, called ParentCamp. While not perfect, the results of this pilot show promise that the use of technology doesn’t have to be a barrier to equity. Virtual tools show promise for expanding opportunities for families to have direct access to educators to learn and ask questions about how to support their children.
Keywords: virtual family engagement; family engagement; English Language Learners